Experimental Study on Rebar Corrosion Using the Galvanic Sensor Combined with the Electronic Resistance Technique - Yunze Xu; Kaiqiang Li; Liang Liu; Lujia Yang; Xiaona Wang; Yi Huang (Sensors, 2016)
In this paper, a new kind of carbon steel (CS) and stainless steel (SS) galvanic sensor system was developed for the study of rebar corrosion in different pore solution conditions. Through the special design of the CS and SS electronic coupons, the electronic resistance (ER) method and zero resistance ammeter (ZRA) technique were used simultaneously for the measurement of both the galvanic current and the corrosion depth. The corrosion processes in different solution conditions were also studied by linear polarization resistance (LPR) and the measurements of polarization curves. The test result shows that the galvanic current noise can provide detailed information of the corrosion processes. When localized corrosion occurs, the corrosion rate measured by the ER method is lower than the real corrosion rate. However, the value measured by the LPR method is higher than the real corrosion rate. The galvanic current and the corrosion current measured by the LPR method shows linear correlation in chloride-containing saturated Ca(OH)2 solution. The relationship between the corrosion current differences measured by the CS electronic coupons and the galvanic current between the CS and SS electronic coupons can also be used to evaluate the localized corrosion in reinforced concrete.